Information and communications technology acceptance by youth entrepreneurs in rural Malaysian communities: the mediating effects of attitude and entrepreneurial intention - Zaremohzzabieh, Zeinab; Abu Samah, Bahaman; Muhammad, Mahazan; Omar, Siti Zobidah; Bolong, Jusang; Hassan, Md. Salleh; Mohamed Shaffril, Hayrol Azril (Routledge, 2016)
This study aims to examine information and communication technology (ICT) acceptance among youth entrepreneurs in rural Malaysian communities by employing two tailored technology acceptance models based on attitudes (AT) and entrepreneurial intention (EI) that influence actual use (AU). The study involved 400 rural youth entrepreneurs selected from four states in Malaysia, and both mediating effects were analyzed using bootstrapping procedures through structural equation modeling. The two models were tested, and vary in terms of different conceptualization of the pathways of mediating entrepreneurship latent factors. The models in the present paper are closely related to the model in a prior study that used the same data set [Zaremohzzabieh et al., 2015. A test of the technology acceptance model for understanding the ICT adoption behavior of rural young entrepreneurs. International Journal of Business and Management, 10(2), 158–169.]. The results revealed that the first model is better than the second model. The results also revealed that the confirmatory strength of the two models improved the initial TAM through some form of mediating effects (i.e. AT and EI). The outcomes of this study contribute to our theoretical understanding of variables that influence ICT acceptance, and inform practice by recognizing methods to improve ICT acceptance among rural youth entrepreneurs in the country. The results provide new insights for small rural businesses and help to explain ICT acceptance, which is relatively underresearched in these growing nations.